Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
ISI Document Delivery No.: BGG42 Times Cited: 0 Cited Reference Count: 5 Cited References: Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 BROOKS B, 1985, P NATL ACAD SCI USA, V82, P4995, DOI 10.1073/pnas.82.15.4995 BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Planken PCM, 2011, J INFRARED MILLIM TE, V32, P975, DOI 10.1007/s10762-011-9824-3 Acbas, Gheorghe Niessen, Katherine A. George, Deepu K. Snell, Edward Markelz, A. G. Proceedings Paper Conference on Ultrafast Phenomena and Nanophotonics XVII Feb 03-06, 2013 San Francisco, CA SPIE, Femtolasers Inc Snell, Edward/G-2055-2018; George, Deepu/J-9882-2014 Snell, Edward/0000-0001-8714-3191; George, Deepu/0000-0003-0021-0705; Markelz, Andrea/0000-0003-0443-4319 National Science Foundation MRI2 [DBI2959989] We thank the National Science Foundation MRI2 grant DBI2959989 for support. 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x 862305
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz